Chickpea Protein Isolation, Characterization and Application in Muffin Enrichment - Sobhy Ahmed El Sohaimy; Marageta A. Brennan; Amira Galal Darwish; Charles S. Brennan (International Journal of Food Studies, 2020)
The aim of this study was to enhance the nutritional value and the functional characteristics of muffins by enriching with chickpea protein isolate, while keeping their rheological characteristics. Chickpea Protein isolate (CPI) was prepared by alkaline solubilization (pH 11), followed by isoelectric precipitation at pH 4.5. SDS-PAGE revealed three subunits with molecular weights of 47, 30 and 85 kDa; representing the globulin fractions, legumin-like and vicilin-like proteins. Maximum protein solubility (83.32%) was obtained at pH 11. CPI exhibited an emulsifying activity index of 25.17 m2 g-1, emulsion stability index of 14.09 min. The foaming capacity and stability were 62% and 94.49%, respectively. Water and oil absorption were 3.65 and 2.30 mL g-1, respectively. CPI was added to muffin batter at 0, 2.5, 5, 7.5 and 10%. CPI fortifieded muffins showed reduction in moisture content, which influenced texture profile analysis through increasing hardness, gumminess and chewiness values. Additionally, both protein content and protein digestibility of muffins increased to 22.2 and 94.08%, respectively. CPI-enriched muffins were darker (lower L) with yellowish crumbs (higher b). Finally, preliminary sensory evaluation showed high consumer acceptance for CPI-enriched muffins.